ALGEBRA - generating simple equations DARTBOARD MATHS ALGEBRA - generating simple equations Dave Carden Liverpool Maths Team
20 X + 5 = 7 5 x 1 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m X = 2 m 2 y 1 2 3
20 X + 2 = 8 5 x 2 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m X = 6 m 2 y 1 2 3
20 y + 4 = 8 5 x 3 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m y = 4 m 2 y 1 2 3
20 k + 3 = 11 5 x 4 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m k = 8 m 2 y 1 2 3
20 m + 11 = 20 5 x 5 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m m = 9 m 2 y 1 2 3
20 2m + 5 = 11 5 x 6 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m m = 3 m 2 y 1 2 3
20 3m + 5 = 20 5 x 7 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m m = 5 m 2 y 1 2 3
20 2m + 2 = 22 5 x 8 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m m = 10 m 2 y 1 2 3
20 2X + 5 = 15 5 x 9 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m X = 5 m 2 y 1 2 3
20 2K + 11 = 21 5 x 10 2 7 x 2m y 2 4 y 1 k 1 8 2 x 3 5 m K = 5 m 2 y 1 2 3
In these simple equations, x is either 1 , 2 , 3 , 4 or 5 X + 2 = 5 so x = X + 1 = 6 so x = X + 4 = 8 so x = X + 3 = 7 so x = X - 3 = 1 so x = X - 1 = 4 so x = 4 - X = 0 so x = X - 2 = 1 so x = 7 – X = 5 so x = 8 – X = 5 so x =
In these simple equations, x is either 1 , 2 , 3 , 4 or 5 X + 2 = 5 so x = X + 1 = 6 so x = 4 X + 4 = 8 so x = 4 X + 3 = 7 so x = X - 3 = 1 so x = 4 X - 1 = 4 so x = 5 4 - X = 0 so x = 4 X - 2 = 1 so x = 3 7 – X = 5 so x = 2 8 – X = 5 so x = 3
In these simple equations, x is either 1 , 2 , 3 , 4 or 5 B In these simple equations, x is either 1 , 2 , 3 , 4 or 5 2X + 1 = 5 so x = 2X + 2 = 6 so x = 3X - 1 = 5 so x = 4X - 3 = 5 so x = 2X - 3 = 3 so x = 2X - 1 = 9 so x = 4 - 2X = 0 so x = 5X - 2 = 1 3 so x = 7 – 2X = 1 so x = 8 – 4X = 0 so x =
In these simple equations, x is either 1 , 2 , 3 , 4 or 5 B In these simple equations, x is either 1 , 2 , 3 , 4 or 5 2 2 2X + 1 = 5 so x = 2X + 2 = 6 so x = 2 3X - 1 = 5 so x = 2 4X - 3 = 5 so x = 3 2X - 3 = 3 so x = 2X - 1 = 9 so x = 5 2 4 - 2X = 0 so x = 5X - 2 = 1 3 so x = 3 3 7 – 2X = 1 so x = 8 – 4X = 0 so x = 2
C Challenge X – 2 = -1 so x = X – 3 = -1 so x = X – 4 = -2 so x =
Challenge 1 2 1 1 3 X – 2 = -1 so x = X – 3 = -1 so x =